Strategy Of Curriculum Development Based On Project Based Learning (Case Study : SMAN 1 Tanta Tanjung Tabalong South Of Kalimantan) - Agustin, Rima Sri; Puro, Sarjono (Sebelas Maret University, 2016)
Curriculum Development must be continuously assessed and developed appropriate to the circumstances by taking into account the challenges that exist so that the directions of development are aligned answer the challenges future. This research aimed: (1) to identification of school potential, mapping and grouping of school experiences, (2) making time line of activity and setting of development method, and (3) curriculum documentation. The subject of research conducted in SMAN 1 Tanta in Tanjung Tabalong South of Kalimantan. Techniques of collecting data used were observation, interview, and document analysis. The data analysis method employed was an interactive model of qualitative analysis. Results of collecting data through observation found unproductive land in the school yard, and there are several local potential that can be used as a basic for curriculum development, interviews with teachers and students that the school requires an integrated between the curriculums with teaching learning activities. Dokumem curriculum in the schools has not shown the existence of curriculum development. Facilitation is done in curriculum development through the implementation of project based learning. The data analysis method employed was an interactive model of qualitative analysis. Curriculum development results showed that: (1) the potential of the school and school experiences: the school garden and organic farming project activities, (2) the school has a distinctive curriculum documentation.